Prediction models for development of hepatocellular carcinoma in chronic hepatitis B patients - Guo, Jiang (World J Clin Cases, 2021)
Chronic hepatitis B (CHB)-related hepatocellular carcinoma (HCC) is a major health problem in Asian-Pacific regions. Antiviral therapy reduces, but does not completely prevent, HCC development. Thus, there is a need for accurate risk prediction to assist prognostication and decisions on the need for antiviral therapy and HCC surveillance. A few risk scores have been developed to predict the occurrence of HCC in CHB patients. Initially, the scores were derived from untreated CHB patients. With the development and extensive clinical application of nucleos(t)ide analog(s) (NA), the number of risk scores based on treated CHB patients has increased gradually. The components included in risk scores may be categorized into host factors and hepatitis B virus factors. Hepatitis activities, hepatitis B virus factors, and even liver fibrosis or cirrhosis are relatively controlled by antiviral therapy. Therefore, variables that are more dynamic during antiviral therapy have since been included in risk scores. However, host factors are more difficult to modify. Most existing scores derived from Asian populations have been confirmed to be accurate in predicting HCC development in CHB patients from Asia, while these scores have not offered excellent predictability in Caucasian patients. These findings support that more relevant variables should be considered to provide individualized predictions that are easily applied to CHB patients of different ethnicities. CHB patients should receive different intensities of HCC surveillance according to their risk category.